(NmIRGOROD(B: [(NpOWESTI(B] / s (N~ASTX (B2s - (NgOGOLX(B, (NnIKOLAJ wASILXEWI^s ((NmOSKWA(B: s (NhUDOVESTWENNAQ LITERATURA(B, s, 1984)
(NtOM SODERVIT POWESTI gOGOLQ (B"(NsTAROSWETSKIE POME]IKI(B", "(NtARAS bULXBA(B", "(NwIJ(B" (NI DR(B., (NSOSTAWIW[IE CIKL(B, (NNAZWANNYJ AWTOROM (B"(NmIRGOROD(B".s
rus
Keywords: (NpOWESTI I RASSKAZYs